2015
DOI: 10.1038/bmt.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in allogeneic hematopoietic cell transplantation outcomes among African Americans and whites

Abstract: The impact of race on outcome has been identified in a number of cancers, with African Americans having poorer survival compared with whites. We conducted a study to investigate the association of race with allogeneic hematopoietic cell transplant (HCT) outcomes. We identified 789 patients (58 African Americans and 731 whites) who underwent allogeneic HCT for hematologic disorders. There were no significant differences between African Americans and white patients in gender, performance status or comorbidity sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…COPD defined through spirometry was included in predictive models for FEV1 as a co‐morbidity that is generally mild in this population and thus is not comprehensively captured by the HCT‐CI. Ethnicity/race was not evaluated as it has not been shown to impact alloHCT outcomes to this point in US‐based populations 29 . Analyses were completed using IBM SPSS Statistics for Windows version 23.0 (SPSS, Chicago, IL), and results were considered significant at the P < 0.05 level.…”
Section: Population and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD defined through spirometry was included in predictive models for FEV1 as a co‐morbidity that is generally mild in this population and thus is not comprehensively captured by the HCT‐CI. Ethnicity/race was not evaluated as it has not been shown to impact alloHCT outcomes to this point in US‐based populations 29 . Analyses were completed using IBM SPSS Statistics for Windows version 23.0 (SPSS, Chicago, IL), and results were considered significant at the P < 0.05 level.…”
Section: Population and Methodsmentioning
confidence: 99%
“…Ethnicity/race was not evaluated as it has not been shown to impact alloHCT outcomes to this point in US-based populations. 29 Analyses were completed using IBM SPSS Statistics for Windows version 23.0 (SPSS, Chicago, IL), and results were considered significant at the P < 0.05 level.…”
Section: Statisticsmentioning
confidence: 99%
“…While the collection of data from only a single institution limits our sample size and may limit generalizability of findings, it also eliminates center variation as a possible source of confounding. This is relevant when considering that two multicenter studies of racial disparities in adult HCT found differences in survival by race, 18,20 but two single‐center studies did not 21,22 . Given the lack of published data regarding pediatric HCT outcomes by race and SES, our findings necessarily require validation and further study.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, two subsequent studies reported worse OS in black patients undergoing HCT, but no differences between Hispanic and white patients 19,20 . More recently, two single‐center studies published in 2015 observed no differences in survival after HCT based on race or ethnicity 21,22 . Results from studies investigating the impact of SES on outcomes in adult HCT are also inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Race and ethnicity have been linked to differences in genetic predispositions to disease [8][9][10][11]. Now that targeted therapies and personalized approaches to diseases having gene-based variances have become more available, genomically-informed approaches are increasingly important among special populations [12][13][14][15].…”
Section: Genetic Variances Among Racial/ethnic Groupsmentioning
confidence: 99%